A DIGITALISASI PEMBELAJARAN PAI DENGAN MODEL PJBL BERBASIS CANVA FOR EDUCATION DI SMPN 7 KOTA MOJOKERTO - Ahmad Alfin Khusaini (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2026)
Education is an important thing in this life, the better the education process of a country, the better the civilization of a nation. In the process of education, it is able to form the independent soul of the young generation of a country, and also the process of strengthening the knowledge and skills of that generation, especially Islamic religious education which directs Muslims in a better direction in accordance with the development of the times, currently we are entering the era of digitalization, so the development of the world of education must be able to go hand in hand with technology, besides that the learning models and media used must be in accordance with the interests of students and in accordance with the development of the times. This study uses a qualitative model in searching for information using interviews, observations and documentation. This study produces a conclusion that the use of the Project Based Learning Model is very useful, especially in the learning process accompanied by applications based on Artificial Intelligence in supporting the learning process, such as the use of Canva For education, an application based on photo, video and document editors, this can be a good friend in the digital-based learning process. Students are more motivated, creative, innovative and productive in producing work that is useful for the surrounding environment. if this is utilized properly in Islamic religious education learning in schools, it will accelerate the process of digitalization of education and will have a positive impact on life.